Invesment Development Strategy Analysis at the Office of Invesment and One Stop Services: Analisis Strategi Pengembangan Investasi di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu - Rikhlah, Delvia; Sukmana, Hendra (Indonesian Journal of Public Policy Review, 2023)
Investment or what is called Investment is currently one of the most importantstrategies to increase growth and development in the economic sector in Indonesia. The Government of Indonesia is focusing on increasing investment, both public and private, to boost Indonesia's economic expansion. Especially investment in infrastructure and manufacturing industry. However, in its implementation there are problems, namely the existence of several investors who do not fully understand the online licensing procedures, and there are still many companies or investors who do not carry out Investment Activity Reports (LKPM) making it difficult to control, monitor and supervise.This study aims to describe and analyze the Investment Development Strategy (Study at the Sidoarjo Regency Investment and One Stop Service) and to describe and analyze the constraints of the Investment Development Strategy (Study at the Sidoarjo Regency Investment and One Stop Integrated Service Office). The results of this study indicate that the Investment Development Strategy (Study at the Investment and One Stop Service Office of Sidoarjo Regency), seen from indicator the Organizational Strategy focuses on many aspects so that the investment climate in Sidoarjo Regency improves from year to year with so much potential that exists and also provides direct assistance to companies related to the licensing system. licensing system. Their work cannot be separated from each other because of community institutions and government institutions.